A feasible method of support slimming based on the different thresholds of polar angles in selective laser melting. (5th November 2018) - Zhang, Kaifei; Mao, Zhongfa; Fu, Guang; Zhang, David Z.; Liu, Chao; Li, Zhonghua
Abstract: The large thermal deformation induced by the high temperature gradient severely restricts the threshold level of polar angle in selective laser melting (SLM). As such, different types of support structures are usually added to improve the manufacturing capacity and broaden the application of SLM technology. However, enormous support structures will result in large time consumption, material waste, high labor intensity and inferior surface quality of part. In this research, a feasible method of slimming support structures was presented. Firstly, a series of experiments for exploring the thresholds of polar angles at different azimuth angles relative to the recoating direction of powders were conducted and the effect of powder recoating by scraper on the building of inclined surfaces was analyzed. Then, a generation algorithm of slimmed support structures was proposed based on the varying thresholds of polar angles. In addition, several typical cases demonstrated the usefulness of this method by eliminating the quantities of their support structures by 35% in average. Graphical abstract: Unlabelled Image Highlights: The threshold of polar angle varies with the azimuth angle due to the effect of recoating by scraper. A generation algorithm of slimmed support structures was presented based on the upper change. Several cases have verified the effectiveness of the proposed support-slimming method. This method can be used to coordinate with other optimization methods in selective laser melting.